2010
DOI: 10.1210/en.2010-0422
|View full text |Cite
|
Sign up to set email alerts
|

Rab1 Small GTP-Binding Protein Regulates Cell Surface Trafficking of the Human Calcium-Sensing Receptor

Abstract: The human calcium-sensing receptor (hCaR) is a family-3/C G-protein-coupled receptor that regulates Ca(2+) homeostasis by controlling parathyroid hormone secretion. Here we investigated the role of Rab1, a small GTP-binding protein that specifically regulates protein transport from the endoplasmic reticulum to the Golgi, in cell surface transport of the hCaR. Cell surface expression of hCaR transiently expressed in human embryonic kidney 293 cells was strongly augmented by coexpression of Rab1 and attenuated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…50,59 The role of Rab1 in vesicular transport from ER to Golgi to regulate CaSR transport to the cell surface has been investigated. 52,53 These data demonstrate that transient expression of the dominant negative Rab1N124I mutant and Rab1 siRNA in HeLa and COS-7 cells and in HEK293 cell type inhibited cell-surface expression of the full-length and C-tail-truncated CaSR variants, and endogenous Rab1 is limiting for CaSR transport from the ER to the cell surface in this expression paradigm. CaSR transport in HEK293 cells is Rab1-dependent similar to AT1R, β 2 -AR, and α-1A AR and unlike the α 2B -AR, which uses a nonconventional Rab1-independent pathway in HEK293 cells.…”
Section: Anterograde Trafficking Of Casr Through Secretory Pathwaymentioning
confidence: 74%
See 1 more Smart Citation
“…50,59 The role of Rab1 in vesicular transport from ER to Golgi to regulate CaSR transport to the cell surface has been investigated. 52,53 These data demonstrate that transient expression of the dominant negative Rab1N124I mutant and Rab1 siRNA in HeLa and COS-7 cells and in HEK293 cell type inhibited cell-surface expression of the full-length and C-tail-truncated CaSR variants, and endogenous Rab1 is limiting for CaSR transport from the ER to the cell surface in this expression paradigm. CaSR transport in HEK293 cells is Rab1-dependent similar to AT1R, β 2 -AR, and α-1A AR and unlike the α 2B -AR, which uses a nonconventional Rab1-independent pathway in HEK293 cells.…”
Section: Anterograde Trafficking Of Casr Through Secretory Pathwaymentioning
confidence: 74%
“…Using both Sar1H79G and siRNA specific for Sar1, disruption of endogenous Sar1 function is found to significantly inhibit cell-surface expression of the CaSR, and transient expression of Sar1H79G leads to retention of CaSR in the ER mostly as immature high-mannose type receptor in heterologously expressed cell lines. 52,53 Confocal microscopic analysis revealed that Sar1H79G arrested CaSR in distinct perinuclear compartments. A significant reduction in cell-surface expression of the CaSR is also confirmed quantitatively by intact cell-surface ELISA and by analysis of CaSR signaling efficacy.…”
Section: Anterograde Trafficking Of Casr Through Secretory Pathwaymentioning
confidence: 99%
“…Several proteins interact with the CaSR when the receptor exits from the ER, including p24A (transmembrane emp24 domain trafficking protein 2(TMED2)) [101]; the small GTP-binding protein Sar1 [102]; receptor-activitymodifying proteins (RAMPs) [96]; Rab1 [103]; calmodulin (CaM) [63]; 14-3-3 [104] and Dorfin [90]. p24A binds predominantly to the immature form of the CaSR and cycles between the ER, the ER-Golgi intermediate compartment (ERGIC) and the cis-Golgi membranes [105,106].…”
Section: Trafficking Of the Casr In Cellsmentioning
confidence: 99%
“…RAMPs and Rab1 are small GTP-binding proteins that localize to the cytoplasmic face of organelle membranes. Both of them are found to facilitate the CaSR trafficking from ER to Golgi [96,103]. The 14-3-3 protein is predicted to interact with the arginine-rich domain of the CaSR ( 890 RRxxxxRKR 898 ) and may lead to the retention of the CaSR in the ER [65,104,107].…”
Section: Trafficking Of the Casr In Cellsmentioning
confidence: 99%
“…Overexpression of dominant negative forms of Rab1, knockdown of Rab1 by siRNA, and antibodies to Rab1 all cause dissociation of COPII vesicles and Golgi proteins (18,19,27 (21). In addition Rab1 has been shown to play an obligatory role in the trafficking of G protein coupled receptors to the cell surface (31,32). In melanocytes, Rab1a is localized to the surface of melanosomes and is necessary for anterograde movement along microtubules (13).…”
Section: Rab1 Function In Cellsmentioning
confidence: 99%